PERANCANGAN MEDIA INFORMASI PROGRAM KESEHATAN MASYARAKAT PT FREEPORT INDONESIA - Anastasya, Nabila; Tohir, Mohamad; Yudiarti, Diena (Telkom University, 2024)
PT Freeport Indonesia through its Community Health Development departmentestablished a health program as a corporate social responsibility effort to address health issues in Mimika Regency. However, they are faced with challenges in informing theirhealth program, which requires an appropriate solution. This design aims to create a health program information media that is easily accepted by the local community. Theresearch methods used are observation, interview, and documentation study involving information media theory, design thinking theory, and visual communication designtheory. The result of this research is the design of print-based information media that brings the concept of informative messages with a touch of culture, AIDA communicationstrategy, and visual concepts that are representative of health programs and the identity of the Community Health Development department to the main and supportinginformation media with the aim of creating awareness in the community about health program services offered by PT Freeport Indonesia. Keywords: article, scientific, journal, health, Freeport, CSR, information, Timika